2021
DOI: 10.5603/pjnns.a2021.0011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of neurological patients with coronavirus 2019: an observational study of one centre

Abstract: Background. Since the emergence of coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 (Severe acute respiratory syndrome coronavirus 2) in Wuhan, China, it has been extensively studied by many scientists. Susceptibility to SARS-CoV-2 infection is shown by people of all ages, especially those with different comorbidities. Our goal was to describe the clinical characteristics, treatment, course, and outcome of COVID-19 in patients with pre-existing neurological disorders.Materials and methods. We retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Stroke during COVID-19 was also associated with increased in-hospital mortality in the whole group but not in the prospective cohort, probably due to severe neurological deficit which prevented these patients from filling out the questionnaire. Previous research has shown that chronic neurological comorbidity increases the risk of in-hospital mortality [16,17]. A recent meta-analysis of 18 studies, mostly of retrospective design, revealed that the mortality rate in COVID-19 patients with concomitant stroke was concerning and, especially in relation to ischaemic stroke, higher than would be expected due to stroke itself [18].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke during COVID-19 was also associated with increased in-hospital mortality in the whole group but not in the prospective cohort, probably due to severe neurological deficit which prevented these patients from filling out the questionnaire. Previous research has shown that chronic neurological comorbidity increases the risk of in-hospital mortality [16,17]. A recent meta-analysis of 18 studies, mostly of retrospective design, revealed that the mortality rate in COVID-19 patients with concomitant stroke was concerning and, especially in relation to ischaemic stroke, higher than would be expected due to stroke itself [18].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be very challenging to distinguish between these two conditions as well as to diagnose MG exacerbation during a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [6]. Moreover, it has been shown that pre-existing neurological disorders are associated with a worse prognosis and a high COVID-19 fatality rate [7]. The first case of SARS-CoV-2 infection in Poland was confirmed on 4 March 2020.…”
Section: Introductionmentioning
confidence: 99%
“…We thank Zielińska-Turek et al [1] for providing such valuable evidence. However, we would like to make some comments on a recently described entity which poses a challenge in the management of patients with a neurological history or who present with neurological complications during the course of COVID-19.…”
Section: To the Editorsmentioning
confidence: 95%
“…We read with great interest the article published recently by Zielińska-Turek et al [1] entitled 'Clinical features of neurological patients with coronavirus 2019: an observational study of one centre' , where the authors investigated a cohort of patients with COVID-19 and previous neurological diseases, finding that most of these patients were elderly, with dementia or a history of stroke, and that these conditions associated with COVID-19 worsened the prognosis and increased the mortality of these patients.…”
Section: To the Editorsmentioning
confidence: 99%
See 1 more Smart Citation